MUDIK DAN KERETAKAN BUDAYA - Iriyanto, Agus Maladi (Faculty of Humanities, Diponegoro University, 2012)
Returning to hometown phenomenon has became a tradition in Indonesia. That tradition is considered as the most effective movement to contribute fund to the rural area. Returning to hometown is accelerating money distribution from urban area to rural area. The tradition of returning to hometown is happened because of the migration movement from rural area to urban area which then becoming an uncontrollable urbanization. The uncontrollable urbanization is happened because of the poverty matter in the rural area. Meanwhile, the uncontrollable urbanization is also creating poverty in the urban area. That’s because lots of the informal sector workers are farmers who leave their rural area.The tradition of returning to hometown contains the dimensions of spiritual, psychological and social that must be addressed by implementing a cultural heteronomy. The commuters are in the pulling aside condition between the new situation and values and the old situation and values. The tradition of returning to hometown is expressing the strength of the primordial bindings of the urban people, while the urban values should be more mondial characterized. Urban area, for the commuters, are not more just a shelter, while their home is still considered in the rural area where they are coming from. Keywords : Tradition of returning to hometown, poverty, urbanization and cultural heteronomy